(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe HIV/AIDS-related practices and identify some related factors among nursing students at Vinh Medical University in the 2024-2025 academic year. Subjects and methods: A cross-sectional descriptive study was conducted on 284 nursing students at Vinh Medical University from August 2024 to April 2025. Data was collected using a pre-designed questionnaire, a survey form for students to complete themselves. Results and conclusions: The percentage of students with satisfactory HIV/AIDS practices was 48.9%. HIV/AIDS-related practices showed statistically significant differences between age groups ≥ 20 and < 20; between students in their 3rd and 4th years and students in their 1st and 2nd years; between those who received and did not receive information about HIV during their university years; and between those who had the opportunity to encounter someone with HIV/AIDS during their studies (p<0.05).